System simulation of the behaviour of trawl fleet under alternative management policies in the West Coast of Peninsular Malaysia - Moe, Shwe Sin (2016)
The Malaysian trawl fishery is besetting with many issues including overcapacity, overfishing, trash fish landings, IUU fishing etc. The fishery resources in the West Coast of Peninsular Malaysia are alleged to be overexploited due to the rapid development and expansion of the trawl fleets since 1960s. Management policies have been implemented in the hope of attaining sustainable exploitation of the fisheries resources in the region. The zonal licensing scheme was applied to control the overcapacity of trawlers by restricting access through the issuance of vessel licenses. However, problems such as excessive fishing effort and overexploitation of the demersal fish stocks by trawlers, encroachment of trawlers into the inshore areas, and conflicts among traditional fishermen and trawlers still exist in the West Coast of Peninsular Malaysia. In the context of management of trawl fishery in the West Coast of Peninsular Malaysia, the responses of fishers to management measures need to be evaluated in order to predict the appropriate management interventions. Therefore, the study is conducted with the objective to evaluate the impact of alternative management policies on the trawl industry in the West Coast of Peninsular Malaysia. To achieve the above objective, a system simulation model is developed to evaluate the performance of trawl fleets and, based on the results of simulations, management policy recommendation will be proposed for the Zone B and Zone C trawl fishery of the West Coast of Peninsular Malaysia. The system simulation model is developed with the three-way interaction between fish stocks, industry and management measures and is used to simulate and evaluate the performance of fishery. These interactions will be tested in the simulation model, including sensitivity analysis. The interconnection between the three main modules such as biological module, economic module, and industry module is evaluated. Under each main module, the interface variables such as sustainable catch, profit, and effort are computed through the estimation of the relevant parameters in each module. Moreover, the system model is validated in order to get the closely mimic the real world system through the sensitivity analysis. The behavior and performance of the industry are simulated using the system model with two scenarios such as open-access and simulated behavior in response with the alternative management policies. The performance of the industry is evaluated through some key performance variables such as fishing effort, total sustainable catch of the three targetted species groups, total profit and profit per vessel in order to propose the proper combination of the management policy implication in the West Coast trawl fishery in Peninsular Malaysia. The data used in this study include both primary and secondary data for the estimation of the parameters and constants of the mathematical equations. The annual catch and effort data of the three targetted species groups is used from the Annual Fishery Statistics of Department of Fishery, Malaysia. The economic data especially for the cost data such as operation costs: bait, fuel, maintenance, gear replacement or repair and food for the workers, and fixed costs: haul, engine, equipment and the possible opportunity cost of the vessels will be collected from survey data. In Zone B, the open-access simulation result showed that fishing efforts are increasing over time from 2012 until 2062. However, the catches of the targeted species groups are declining and the CPUEs of the three targeted species groups are also decreasing. This condition can be explained due to the unlimited increasing of fishing effort. Even with the increasing of fishing effort, the catches of all target species groups are decreasing. Base on the results of the open-access simulation analysis, this may suggest that the zone B trawl fishery will be overexploited in the long run. The results of policy (1) analysis of reduction in vessel license, the results indicated that decreasing licenses give the decreasing of fishing effort and the higher catch and the proper level of license issued reduction in zone B is policy 1 C and 1D of 30 per cent and 50 per cent license reduction levels. The results of policy (2) of fuel price subsidy reduction showed that there is no significant effect on fishing effort, catches and profits of the industry and this can be seen that fuel price subsidy reduction policy can be low impact to the Zone B trawl fishery. The results of policy (3) of increasing landing charge imposing with different levels showed that increasing landing charge caused the increasing cost and lowered the profit level which in turn reduced the fishing effort. The results of policy (4) analyzes of Zone B showed that the higher catch and also higher profit can be ascertained from policy 4C of 50 percent license reduction coupled with 20 percent fuel price subsidy reduction and 15 percent landing charge. In the numerical expression of proposed policy for zone B trawl fishery, the license issued for the Zone B is 1,500 licenses with 20 per cent fuel price subsidy reduction and the landing charge of 15 percent of total revenue should be imposed in the effort control management of West Coast Zone B trawl fishery from 2012 to 2042. In Zone C, the open-access simulation results showed that fishing efforts are increasing over time until 2062. However, the catches of the targeted species groups are also increasing and decreasing trend was found in only in the later 15 years of simulation from 2047 to 2062. Base on the results of the open-access simulation, this may suggest that Zone C trawl fishery can be regarded as it is not in overexploited condition yet. Therefore, the fishing effort in Zone C can be increased to the certain level which can give higher catch and profit for the industry. The results of policy (1) analysis: increasing in vessel licenses, showed that the proper level of license issued increasing in Zone C is policy 1C and 1 D of 50 percent and 100 percent license increasing from the 2012 level. The policy (3) of increased landing charge imposing with different levels showed that the proper level of landing charge percentage should be considered in Zone C of the West coast trawl fishery. The results of policy (4) analyzes showed that increasing license issued gives more catch and get higher profit per vessel, and in this study, 100 % license increasing (policy 4C and 4 D) gives more profit than 50 % license reduction (policy 4A and 4B). Therefore, the proper policy combination for Zone C is policy 4C and it is the combination of 100 % license increasing and 15 percent landing charge. In the numerical expression, the license issued for the Zone C is 1,400 licenses coupled with landing charge of 15 percent of total revenue should be imposed in the effort control management of West Coast Zone C trawl fishery from 2012 to 2042. Base on the results of West Coast trawl fishery, the fish resources in Zone B are overexploited and it is needed to control the fishing effort by reducing the trawl vessels in this area. However, the fish resources in Zone C are not overexploited yet and the potential for the higher catch with increasing fishing effort is still out there. Despite being needed to be banned the trawlers, the option of removing the trawlers from near shore to offshore fishing will be another policy option to ascertain the resource sustainability. From the simulation results from the study indicated that the zone B trawlers should be decreased and whereas of Zone C still can be increased to the certain level. The recommendation for the proposed policy option is to reduce the zone B trawlers and transformed to Zone C licensed trawlers by pushing them to further away from near shore fisheries. Therefore, the viable policy option is to transfer the excess trawl fishing fleet from Zone B to Zone C without adversely affecting the socioeconomic conditions of trawlers in Zone B. However, the success of the policy recommendation in this study requires the perfect enforcement by the management authorities. The limitation of the license issued for the trawl vessels might be the minimum bound of the number of vessels and the number of vessels might be higher than the recommended values because of the IUU fishing in this area. Therefore, the strict and perfect enforcement of the policy is critically required in the successful management of the trawl fishery in the West Coast of Peninsular Malaysia.